Purification, characterization and hypoglycemic activity of glycoproteins obtained from pea (Pisum sativum L.) - Gaoyixin Qin; Wu Xu; Junping Liu; Liyan Zhao; Guitang Chen (Food Science and Human Wellness, 2021)
This study aimed to isolate and characterize the structures of glycoproteins from peas and determine their hypoglycemic activity. The crude pea glycoproteins (PGP) were extracted by hot water and purified by diethylaminoethyl (DEAE)-Sepharose chromatography and Sephadex G-100 size-exclusion chromatography in sequence. Then three main fractions were obtained, namely PGP1, PGP2 and PGP3, with molecular weights of 897 615, 846 740 and 1 194 692 Da, respectively. The physical and chemical properties of the three fractions were evaluated and compared by Fourier transform infrared spectroscopy (FT-IR), nuclear magnetic resonance (NMR), scanning electron microscope (SEM), high performance liquid chromatography (HPLC) and other analytical techniques. The fraction PGP2 with the highest hypoglycemic activity, was screened using the Caco-2 monolayer cell model. It can inhibit the uptake of glucose in the small intestine, as well as the activities of maltase and sucrase. After simulated gastrointestinal digestion, PGP2 significantly enhanced the inhibitory effect of α-glucosidase, and slightly reduced the inhibitory ability of α-amylase. In summary, PGP2 possessed strong hypoglycemic activity after digestion. These results indicated that PGP2 has the potential to be developed into a functional food or natural medicine for the treatment of type 2 diabetes mellitus.